Molecular characterization of Richter syndrome identifies de novo diffuse large B-cell lymphomas with poor prognosis - Broséus, Julien; Hergalant, Sébastien; Vogt, Julia; Tausch, Eugen; Kreuz, Markus; Mottok, Anja; Schneider, Christof; Dartigeas, Caroline; Roos-Weil, Damien; Quinquenel, Anne; Moulin, Charline; Ott, German; et al. (Nature Communications, 2023)
Richter syndrome (RS) is the transformation of chronic lymphocytic leukemia (CLL) into aggressive lymphoma, most commonly diffuse large B-cell lymphoma (DLBCL). We characterize 58 primary human RS samples by genome-wide DNA methylation and whole-transcriptome profiling. Our comprehensive approach determines RS DNA methylation profile and unravels a CLL epigenetic imprint, allowing CLL-RS clonal relationship assessment without the need of the initial CLL tumor DNA. DNA methylation- and transcriptomic-based classifiers were developed, and testing on landmark DLBCL datasets identifies a poor-prognosis, activated B-cell-like DLBCL subset in 111/1772 samples. The classification robustly identifies phenotypes very similar to RS with a specific genomic profile, accounting for 4.3-8.3% of de novo DLBCLs. In this work, RS multi-omics characterization determines oncogenic mechanisms, establishes a surrogate marker for CLL-RS clonal relationship, and provides a clinically relevant classifier for a subset of primary “RS-type DLBCL” with unfavorable prognosis.
Gesehen am 30.08.2023